PENGGUNAAN MEDIA PERMAINAN KARTU DOMINO UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDUKSI OKSIDASI DI KELAS X SMA NEGERI 10 PEKANBARU - Jayanti, Elda; Azmi, Johni; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about the use of domino card game media has been conducted in SMA Negeri 10 Pekanbaru. The purpose of this research is to improve the student achievement on the subject oxsidation reduction reaction in class X SMA Negeri 10 Pekanbaru. The type of this research is experimental research with experiment design randomized control group pretest-posttest. Sample of the research consisted of two classes, a class X.3 as an experimental class (use domino card game media) and class X.2 as the control class (without domino card game media). T-test was used as analysis technique. Based on the data analysis obtained t > t table i.e 3,24>1.66, so it can be concluded that use domino card game can improve the student achievement on the subject of oxidation reduction reactions in class X SMA Negeri 10 Pekanbaru up to 10,45%.Keywords: Learning Achievement, Domino Card Game